PROPERTY AND LIABILITY INSURANCE DEMAND IN THE CZECH REPUBLIC - Robin Koklar (European Scientific Journal, ESJ, 2013)
The objective of this study is to investigate empirically the relationship between property and liability insurance industry and macroeconomic and financial determinants in the Czech Republic. Further objective was to analyze selected factors that have an impact on loss ratio to verify the existence of capacity constraint theory. Estimation results revealed that Czech GDP does not have an impact on property and liability insurance, which might be caused by relatively undeveloped financial system. There was found a negative effect of gross capital formation on non life gross premium underwritten, that was probably caused by substitution effect, when company investment replaces the purchase of non-life insurance. Surprisingly, even household consumption was found to have a negative impact on non-life real gross premium. On the other hand, employment had a positive effect on real gross premium, which was in line with theory, since higher employment increases income that can be spent on property and liability insurance. Estimation results of OLS regression suggest that non life insurance cycles in the Czech Republic cannot be explained by capacity constraint theory.